Assessment of Drinking Water Quality of Renukoot Industrial Area in District Sonbhadra, Uttar Pradesh - Bharati, D. K.; Singh, M. B. (National Geographical Journal of India, 2022)
The drinking water quality of Renukoot Industrial Area of Sonbhadra district of state Uttar Pradesh in India has been studied. For this study, the ground water samples were collected from the selected locations of the study area with the identification of their longitude and latitude. The GIS locations of the sampling sites are shown in map. Further, the samples were analyzed as per guidelines of BIS for 14 drinking water quality parameters like pH, Total Hardness, Alkalinity, Chloride, TDS, Sulfate, Nitrate, etc. in analytical laboratory. The results are compared with Indian Standard Drinking Water specification IS: 10500-2012. The study reveals that the concentration of major constituents in the water samples is well within the permissible limits of the drinking water except in few cases where concentration of one or more parameters are high which indicates that the water of the study area is fit for drinking purposes in most of the places except few sites. Further, correlation coefficient values indicate the presence of NaCl and KCl salts in such ground waters and high values of TDS are mainly due to presence of NaCl and KCl.